Development of An On-Board Diagnostics System Based On Wireless Network - Guosheng Feng; Bo Feng; Sumei Jia; Lisha Feng (Institute of Advanced Engineering and Science, 2014)
In order to control vehicle exhaust emission effectively, an OBD is developed based on Zigbee technology. Overall solution design of the system is proposed and the vehicle-mounted monitoring database is established. The wireless network communication hardware platform is set up by the MC9S08GT60 microcontroller and the MC13192 wireless module. The project document is produced with the help of BeeKit wireless connectivity toolkit. Under the CodeWarrior IDE development environment, the monitoring station coordinator networking program and the vehicle-mounted terminal device networking program are designed. Experimental results shows that this system complete data exchange between the monitoring station coordinator and the vehicle-mounted terminal device and transfer data into monitoring station computer. The wireless network of OBD is realized. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4687